Nanoesferas de sílica recobertas por carbono: um novo suporte para catalisadores de Fischer-Tropsch - Bulcão, Nina Wargas de Faria Roma (2019)
The main objective of this work is the preparation of silica nanospheres coated with carbon layers of different thicknesses (20 nm and 30 nm) and their use as a new support for Fischer-Tropsch (FT) reaction. Cobalt (5% m/m) was used as active phase. Some oxides are the common supports employed in FT reaction, and they can strongly interact with the active phase, leading to the formation of mixed inactive compounds. In order to decrease metal-support interaction, carbon support was used, while silica nanospheres contribute for mechanical resistance of the material and controls carbon layer thickness. Microscopy results proved the formation of different thicknesses of carbon layers deposited over silica nanospheres. The influence of the carbon layers in activity and selectivity in Fischer-Tropsch synthesis (FTS) was evaluated, and the results indicated that its presence reduced C26 + formation, favoring light hydrocarbons formation, including gasoline and diesel. The difference in the thicknesses of carbon layers showed no influence on the formation of products in the FTS. After that, the carbon layer was functionalized by introduction of acid groups with H2O2 (30%), and it was verified that acidity promoted cracking of the heavy products in the C26 + range.